Level of knowledge of prevention of blood-borne infectious diseases among Master's degree students of nursing - Lidia Sierpińska; Katarzyna Skowronek; Anna Jedynak (Kazimierz Wielki University, 2024)
Introduction. Blood-borne infections are a serious problem among medical staff, especially nursing staff, because nurses have the most frequent contact with patients. As future employees of health care, students of nursing are exposed to a number of hazardous factors. Work with patients of unknown serological status (during practical classes and apprenticeships) is associated with the risk of infection with various pathogens.   Objective. The aim of the study was recognition of the level of knowledge concerning prevention of blood-borne infectious diseases among Master's degree students of nursing. Material and Methods. The study was conducted in the second half of 2022 among 104 Master's degree students of nursing, who were educated at the Radom School in Radom, by the method of a diagnostic survey, using an author-constructed questionnaire. Results. The majority of the examined students (96.2%) knew what diseases are transmitted through blood. More than a half of respondents (63.5%) evaluated their level of knowledge about blood-borne diseases as mediocre, and 19.2% - as low. A part of respondents (67.3%) had knowledge that trace amounts of blood are enough to cause infection with blood-borne diseases. All students in the study knew the main methods of prevention of infections transmitted via blood, and the deficit of knowledge concerned proper use of personal protection equipment (5.8%) and the observance of the procedure to be followed in the event of occupational exposure (3.8%). A large group of respondents (82.7%-100.0%) knew various risk factors of infection with blood-borne diseases. The majority of respondents (88.5%) knew that there is an effective vaccine against hepatitis B, but 43.3% of the students in the study did not know the main symptoms of infection with HBV. Students most often knew (90.4%) how to diagnose infection with HCV - anti-HCV test for the presence of antibodies against hepatitis C virus in blood; however, 26.9% of respondents were not aware that there is no vaccine against hepatitis C. The majority of the examined students (84.7%) knew early symptoms of infection with HIV, while the remainder had a deficit of knowledge in this area. A large group of respondents (82.0%-94.0%) knew various risk factors of infection with HIV. Conclusions. Students of nursing should be motivated to expand their knowledge concerning prevention of blood-borne diseases, observance of the principles of personal protection, prevention of occupational exposure, and proper post-exposure prophylaxis.